Electrolyte, electrolyte, preparation method of electrolyte and lithium ion battery
By using an electrolyte containing fluorine-containing monomers in lithium-ion batteries, and reducing the viscosity and increasing polarity of the electrolyte through specific organic solvent ratios, the problem of poor uniform infiltration of the electrolyte solution in traditional lithium-ion batteries is solved, and the electrochemical performance and safety of the battery are improved.
Patent Information
- Application Number
- CN202411947158.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-29
AI Technical Summary
Traditional liquid lithium-ion batteries have great safety risks due to the presence of combustible liquid electrolytes. The electrolyte has a large viscosity and low polarity, which leads to the unsatisfactory effect of uniformly infiltrating the battery cell, affecting the electrochemical performance of the battery.
An electrolyte solution is provided, including a polymer monomer and an organic solvent. The polymer monomer contains a fluorine-containing monomer. The organic solvent consists of a first solvent, a second solvent and a third solvent. The viscosity of the first solvent is 0.1-0.6 mPa.s, the dielectric constant of the second solvent is 20-100, and the third solvent is a fluorine-containing solvent. Through synergistic action, the overall viscosity of the electrolyte is reduced and the polarity is improved, and the solubility and dispersion of the fluorine-containing monomer are enhanced.
It improves the effect of the electrolyte to uniformly penetrate the battery cell, enhances the polarity and dissolution ability of the electrolyte, and improves the electrochemical performance and safety of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrolyte, an electrolyte and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries with high energy density, high power density, long life and no memory are widely used in smart homes, smart wearables, smart communication tools, the Internet of Everything and other scenarios. However, traditional liquid lithium-ion batteries have great safety risks due to the presence of flammable liquid electrolytes; gel electrolytes have the advantages of high safety, low production cost and high efficiency, and have attracted widespread attention.
[0003] In the related art, in order to improve the safety of the battery, the electrolyte used to prepare the gel electrolyte usually includes a highly polar fluorinated monomer with a flame retardant effect, and the gel electrolyte is generally prepared by an in-situ curing method after liquid injection, that is, the electrolyte is first injected into the battery cell, the electrolyte is fully infiltrated into the battery cell, and then the gel electrolyte is formed in the battery cell by in-situ heating and curing. However, due to the high viscosity and low polarity of the electrolyte, the solubility of the fluorinated monomer in the electrolyte and the diffusivity in the battery cell are poor, and the effect of the electrolyte uniformly infiltrating the battery cell is not ideal, which affects the electrochemical performance of the battery. Summary of the invention
[0004] The embodiments of the present invention provide an electrolyte, an electrolyte and a preparation method thereof, and a lithium-ion battery, which can improve the technical problem that the electrolyte has an unsatisfactory effect of uniformly wetting a battery cell due to high viscosity and low polarity of the electrolyte.
[0005] In a first aspect, an embodiment of the present invention provides an electrolyte, comprising: a polymer monomer and an organic solvent;
[0006] The polymer monomer includes a fluorine-containing monomer;
[0007] The organic solvent comprises a first solvent, a second solvent and a third solvent, the viscosity of the first solvent is 0.1-0.6 mPa.s, the dielectric constant of the second solvent is 20-10, and the third solvent is a fluorine-containing solvent;
[0008] Taking the total volume of the organic solvent as 100%, the volume percentage of the first solvent in the organic solvent is 30%-80%, the volume percentage of the second solvent in the organic solvent is 5%-50%, and the volume percentage of the third solvent in the organic solvent is 5%-40%.
[0009] In one embodiment, the mass percentage of the organic solvent in the electrolyte is 40%-84%.
[0010] In one embodiment, the first solvent comprises at least one of acetonitrile, propionitrile, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, ethyl acetate, methyl acetate, methyl formate, ethyl formate, propyl formate, isopropyl formate, dimethanol formal, ethylene glycol dimethyl ether, and ethylene glycol ethyl formate; and / or
[0011] The second solvent comprises at least one of methylglutaronitrile, glutaronitrile, adiponitrile, succinonitrile, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfone, dimethyl sulfoxide, diethyl sulfone, and sulfolane; and / or
[0012] The third solvent includes at least one of ethyl fluoroacetate, ethyl difluoroacetate, ethyl trifluoroacetate, N,N-dimethyltrifluoroacetamide, trifluorobenzene, 1,2,3,5-tetrafluorobenzene, α,α,α-trifluorotoluene, 1,2-difluorobenzene, 1,3-difluorobenzene, fluoroethylene carbonate, 2,3-difluorophenyl ether, 2-trifluoromethyl ethylene oxide, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether, methyl nonafluorobutyl ether, 1,1,1,2,3,4,4,5,5,5-decafluoro-3-methoxy-2-trifluoromethylpentane, trimethylsilyl trifluoromethanesulfonate, and dimethoxymethyl (3,3,3-trifluoropropyl) silicon.
[0013] In one embodiment, the mass percentage of the polymer monomer in the electrolyte is 5%-60%; and / or
[0014] The mass percentage of the fluorine-containing monomer in the polymer monomer is 30%-70%; and / or
[0015] The fluorine-containing monomer includes at least one of 2,2-trifluoroethyl methacrylate, 2,2,2-trifluoroethyl acrylate, 1,1,1,3,3,3-hexafluoropropane-2-yl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 2,2,3,3-tetrafluoropropyl acrylate, 2,2,3,3,3-pentafluoropropyl acrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, hexafluorobutyl methacrylate, hexafluoroisopropyl acrylate, and 2,2,3,3,4,4,4-heptafluorobutyl methacrylate; and / or
[0016] The polymer monomers further include silicon-containing monomers and / or sulfur-containing monomers.
[0017] In one embodiment, the silicon-containing monomer includes at least one of vinyltrimethoxysilane, dimethoxy(methyl)(vinyl)silane, vinyltriethoxysilane, vinyltriisopropoxysilane, methoxydimethyl(vinyl)silane, methylvinyldiethoxysilane, vinyldimethylethoxysilane, allyltrimethoxysilane, tri(2-methoxyethoxy)vinylsilane, vinyloxytrimethylsilane, allyltriethoxysilane, trimethoxy(7-octen-1-yl)silane, isopropenyloxytrimethylsilane, trimethyl((2-methylprop-1-en-1-yl)oxy)silane, triphenoxy(vinyl)silane, vinylpentamethyldisiloxane, and vinyltris(trimethylsiloxy)silane; and / or
[0018] The sulfur-containing monomer includes at least one of allyl ethyl sulfide, allyl methyl sulfide, allyl methyl disulfide, allyl propyl disulfide, and diallyl trisulfide; and / or
[0019] The mass percentage of the silicon-containing monomer in the polymer monomer is 30%-70%; and / or
[0020] The mass percentage of the sulfur-containing monomer in the polymer monomer is 0-40%.
[0021] In one embodiment, the electrolyte further includes a cross-linking agent, and the cross-linking agent includes a sulfur-containing cross-linking agent and / or a silicon-containing cross-linking agent.
[0022] In one embodiment, the silicon-containing crosslinking agent includes at least one of trivinylethoxysilane, tetraethoxydivinyldisiloxane, tetramethyldivinyldisiloxane, and tetrakis(dimethylvinylsiloxy)silane; and / or
[0023] The sulfur-containing crosslinking agent includes at least one of diallyl monosulfide, prop-2-ene-1-thiosulfinic acid S-allyl ester, diallyl trisulfide, and N,N-bis(acryloyl)cystamine; and / or
[0024] The mass percentage of the cross-linking agent in the electrolyte is 0.1%-5%.
[0025] In one embodiment, the electrolyte further includes an initiator, a lithium salt, an additive and inorganic conductive particles.
[0026] In one embodiment, the initiator includes at least one of N,N-azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, diethylhexyl oxydicarbonate, benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate; and / or
[0027] The mass percentage of the initiator in the electrolyte is 0.01%-1%; and / or
[0028] The lithium salt comprises at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluorooxalatophosphate, lithium bis(fluorobis(oxalatophosphate), lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, and lithium bis(oxalatoborate); and / or
[0029] The mass percentage of the lithium salt in the electrolyte is 10%-25%; and / or
[0030] The additive comprises at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, methylene disulfonate, vinyl sulfite, polyether sulfone, vinyl sulfate, and propenyl-1,3-sultone; and / or
[0031] The mass percentage of the additive in the electrolyte is 0.1%-5%; and / or
[0032] The inorganic conductive particles include at least one of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate, lithium lanthanum titanate, silicon dioxide, and titanium dioxide; and / or
[0033] The average particle size of the inorganic conductive particles is 5nm-350nm; and / or
[0034] The mass percentage of the inorganic conductive particles in the electrolyte is 0.1%-10%.
[0035] In a second aspect, an embodiment of the present invention provides an electrolyte, wherein the electrolyte is prepared from the electrolyte solution as described above.
[0036] In a third aspect, an embodiment of the present invention provides a method for preparing an electrolyte, comprising the following steps:
[0037] providing an electrolyte as described above;
[0038] The electrolyte is injected into the battery cell, left to stand, and heated to solidify to obtain the electrolyte.
[0039] In one embodiment, the preparation method of the electrolyte comprises the following steps: mixing a polymer monomer, an organic solvent and other raw materials in a formulated amount to obtain the electrolyte;
[0040] Wherein, the polymer monomer includes a fluorine-containing monomer;
[0041] The organic solvent comprises a first solvent, a second solvent and a third solvent, the viscosity of the first solvent is 0.1-0.6 mPa.s, the dielectric constant of the second solvent is 20-100, and the third solvent is a fluorine-containing solvent;
[0042] Taking the total volume of the organic solvent as 100%, the volume percentage of the first solvent in the organic solvent is 30%-80%, the volume percentage of the second solvent in the organic solvent is 5%-50%, and the volume percentage of the third solvent in the organic solvent is 5%-40%.
[0043] In one embodiment, the other raw materials further include a formulated amount of sulfur-containing monomers, silicon-containing monomers, cross-linking agents, initiators, lithium salts, additives and inorganic conductive particles; and / or
[0044] The mixing is carried out in an argon atmosphere or a nitrogen atmosphere, and / or the mixing temperature is 21° C.-25° C., and / or the mixing time is 4 h-24 h; and / or
[0045] The standing temperature is 21°C-25°C, and / or the standing time is 24h-72h; and / or
[0046] The temperature of the heating and curing is 45° C.-120° C., and / or the time of the heating and curing is 4 h-24 h.
[0047] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the electrolyte as described above or an electrolyte prepared by the method as described above.
[0048] Beneficial effects of the embodiments of the present invention:
[0049] In an embodiment of the present invention, the organic solvent of the electrolyte includes a first solvent, a second solvent and a third solvent, the viscosity of the first solvent is 0.1-0.6mPa.s, the dielectric constant of the second solvent is 20-100, the third solvent is a fluorine-containing solvent, and the volume percentage of the first solvent in the organic solvent is 30%-80%, the volume percentage of the second solvent in the organic solvent is 5%-50%, and the volume percentage of the third solvent in the organic solvent is 5%-40%. In the present invention, the viscosity of the first solvent is relatively low, and the first solvent can reduce the overall viscosity and flow resistance of the electrolyte, so that the electrolyte can penetrate into the interior of the battery cell faster and evenly and fully cover various parts of the battery cell, thereby improving the effect of the electrolyte uniformly infiltrating the battery cell; the dielectric constant of the second solvent is 20-100, and the second solvent has a relatively high polarity, which can increase the polarity of the electrolyte, thereby increasing the solubility and dispersibility of fluorinated monomers and other high-polarity components in the electrolyte; the third solvent is a fluorinated solvent, and the fluorinated solvent can further increase the solubility of the fluorinated monomer in the electrolyte. At the same time, the fluorine atoms in the fluorinated solvent can capture free radicals, inhibit the chain reaction of free radical combustion, and further improve the flame retardancy and safety of the battery. The organic solvent includes the first solvent, the second solvent and the third solvent in the above-mentioned formula amount. Through the synergistic effect between the first solvent, the second solvent and the third solvent, the electrolyte has a lower viscosity, the electrolyte can evenly and quickly infiltrate the battery cell, and the wetting effect of the electrolyte is improved. In addition, the organic solvent can increase the solubility and dispersibility of high-polarity components such as fluorinated monomers in the electrolyte. In addition, the organic solvent can also improve the diffusibility of each component in the electrolyte in the battery cell. DETAILED DESCRIPTION
[0050] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In the present invention, unless otherwise specified, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state; while "inside" and "outside" refer to the outline of the device.
[0051] In the related art, the electrolyte has high viscosity and low polarity, resulting in an unsatisfactory effect of uniformly wetting the battery cell with the electrolyte, which needs to be further improved.
[0052] To solve the above problems, an embodiment of the present application provides an electrolyte, comprising: a polymer monomer and an organic solvent; the polymer monomer comprises a fluorine-containing monomer; the organic solvent comprises a first solvent, a second solvent and a third solvent, the viscosity of the first solvent is 0.1-0.6 mPa.s, the dielectric constant of the second solvent is 20-100, and the third solvent is a fluorine-containing solvent; based on the total volume of the organic solvent as 100%, the volume percentage of the first solvent in the organic solvent is 30%-80%, the volume percentage of the second solvent in the organic solvent is 5%-50%, and the volume percentage of the third solvent in the organic solvent is 5%-40%. In this embodiment, the organic solvent of the electrolyte includes a first solvent, a second solvent and a third solvent, the viscosity of the first solvent is 0.1-0.6mPa.s, the dielectric constant of the second solvent is 20-100, the third solvent is a fluorine-containing solvent, and the volume percentage of the first solvent in the organic solvent is 30%-80%, the volume percentage of the second solvent in the organic solvent is 5%-50%, and the volume percentage of the third solvent in the organic solvent is 5%-40%. In the present invention, the viscosity of the first solvent is relatively low, and the first solvent can reduce the overall viscosity and flow resistance of the electrolyte, so that the electrolyte can penetrate into the interior of the battery cell faster and evenly and fully cover various parts of the battery cell, thereby improving the effect of the electrolyte uniformly infiltrating the battery cell; the dielectric constant of the second solvent is 20-100, and the second solvent has a relatively high polarity, which can increase the polarity of the electrolyte, thereby increasing the solubility and dispersibility of fluorinated monomers and other high-polarity components in the electrolyte; the third solvent is a fluorinated solvent, and the fluorinated solvent can further increase the solubility of the fluorinated monomer in the electrolyte. At the same time, the fluorine atoms in the fluorinated solvent can capture free radicals, inhibit the chain reaction of free radical combustion, and further improve the flame retardancy and safety of the battery. The organic solvent includes the first solvent, the second solvent and the third solvent in the above-mentioned formula amount. Through the synergistic effect between the first solvent, the second solvent and the third solvent, the electrolyte has a lower viscosity, the electrolyte can evenly and quickly infiltrate the battery cell, and the wetting effect of the electrolyte is improved. In addition, the organic solvent can increase the solubility and dispersibility of high-polarity components such as fluorinated monomers in the electrolyte. In addition, the organic solvent can also improve the diffusibility of each component in the electrolyte in the battery cell.
[0053] In the present embodiment, the viscosity of the first solvent refers to the viscosity at room temperature (25 ± 5 ° C), which has a well-known meaning in the art and can be tested using instruments and methods known in the art. Optionally, the viscosity of the first solvent can be any one of 0.1mPa.s, 0.2mPa.s, 0.3mPa.s, 0.4mPa.s, 0.5mPa.s, 0.6mPa.s, etc. or a range between any two. In the present invention, if the viscosity of the first solvent is too low, it is easy to cause the overall viscosity of the electrolyte to be too low, the particles in the electrolyte are prone to sedimentation, and the stability of the electrolyte is reduced; if the viscosity of the first solvent is too high, it is easy to cause the overall viscosity of the electrolyte to be too high, increase the flow resistance and ion transfer resistance of the electrolyte, and the electrolyte has an unsatisfactory wetting effect on the battery cell.
[0054] In this embodiment, the dielectric constant of the second solvent refers to the dielectric constant at room temperature (25 ± 5 ° C), which has a well-known meaning in the art and can be tested using instruments and methods known in the art. Optionally, the dielectric constant of the second solvent can be any one of 20, 30, 40, 50, 60, 70, 80, 90, 100, etc. or a range between any two. In the present invention, if the dielectric constant of the second solvent is too low, it is easy to cause the polarity of the electrolyte to be too low, and the solubility of high-polarity components such as fluorinated monomers in the electrolyte in the electrolyte becomes poor; if the dielectric constant of the second solvent is too high, it is easy to cause the polarity of the electrolyte to be too high, increasing the resistance to ion transmission.
[0055] Optionally, the volume percentage of the first solvent in the organic solvent may be any one of 30%, 40%, 50%, 60%, 70%, 80%, etc. or a range between any two. In the present invention, if the content of the first solvent is too little, it is easy to cause the viscosity of the electrolyte to be too high, increase the flow resistance, ion transfer resistance and battery discharge polarization of the electrolyte, and the electrolyte has an unsatisfactory wetting effect on the battery cell; if the content of the first solvent is too much, it will reduce the polarity of the electrolyte and the high-rate discharge performance of the battery.
[0056] Optionally, the volume percentage of the second solvent in the organic solvent can be any one of 5%, 10%, 15%, 20%, 30%, 35%, 40%, 45%, 50%, etc. or a range between any two. In the present invention, if the content of the second solvent is too much, it is easy to cause the polarity and viscosity of the electrolyte to be too high, increase the flow resistance, ion transfer resistance and battery discharge polarization of the electrolyte, and affect the low temperature performance and high rate discharge performance of the battery; if the content of the second solvent is too little, it is easy to cause the dielectric constant of the electrolyte to be too low, and it is easy to reduce the solubility and dispersibility of high polar components such as fluorinated monomers in the electrolyte, affecting the high rate discharge performance of the battery.
[0057] Optionally, the volume percentage of the third solvent in the organic solvent may be any one of 5%, 10%, 15%, 20%, 30%, 35%, 40%, etc., or a range between any two. In the present invention, if the content of the third solvent is too much, it is easy to cause the battery cycle performance to decline; if the content of the third solvent is too little, it is easy to cause the solubility of the fluorinated monomer in the electrolyte to decrease, and the diffusion effect of the fluorinated monomer in the battery core is not ideal, which affects the flame retardant performance and safety performance of the battery.
[0058] In one embodiment, the mass percentage of the organic solvent in the electrolyte is 40%-84%. Optionally, the mass percentage of the organic solvent in the electrolyte can be any one of 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 84%, etc., or a range between any two.
[0059] In one embodiment, the first solvent includes at least one of acetonitrile, propionitrile, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, ethyl acetate, methyl acetate, methyl formate, ethyl formate, propyl formate, isopropyl formate, dimethanol formal, ethylene glycol dimethyl ether, and ethylene glycol ethyl formate.
[0060] In one embodiment, the second solvent includes at least one of methylglutaronitrile, glutaronitrile, adiponitrile, succinonitrile, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfone, dimethyl sulfoxide, diethyl sulfone, and sulfolane.
[0061] In one embodiment, the third solvent includes at least one of ethyl fluoroacetate, ethyl difluoroacetate, ethyl trifluoroacetate, N,N-dimethyltrifluoroacetamide, trifluorobenzene, 1,2,3,5-tetrafluorobenzene, α,α,α-trifluorotoluene, 1,2-difluorobenzene, 1,3-difluorobenzene, fluoroethylene carbonate, 2,3-difluorophenyl ether, 2-trifluoromethylethylene oxide, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether, methyl nonafluorobutyl ether, 1,1,1,2,3,4,4,5,5,5-decafluoro-3-methoxy-2-trifluoromethylpentane, trimethylsilyl trifluoromethanesulfonate, and dimethoxymethyl (3,3,3-trifluoropropyl) silicon.
[0062] In one embodiment, the mass percentage of the polymer monomer in the electrolyte is 5%-60%. Optionally, the mass percentage of the polymer monomer in the electrolyte can be any one of 5%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, etc. or a range between any two. In this embodiment, when the mass of the polymer monomer is too much, it is easy to cause the polymer molecular weight to be too high and the mechanical strength of the electrolyte to be too large; when the mass of the polymer monomer is too little, it is easy to cause the polymer molecular weight to be too low, affecting the mechanical properties and electrochemical properties of the battery.
[0063] In one embodiment, the mass percentage of the fluorine-containing monomer in the polymer monomer is 30%-70%. Optionally, the mass percentage of the fluorine-containing monomer in the polymer monomer can be any one of 30%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc. or a range between any two. In this embodiment, when the mass of the fluorine-containing monomer is too much, it is easy to cause the battery cycle performance to decrease; when the mass of the fluorine-containing monomer is too much, it is easy to reduce the flame retardant performance and safety performance of the battery.
[0064] In one embodiment, the fluorine-containing monomer includes at least one of 2,2-trifluoroethyl methacrylate, 2,2,2-trifluoroethyl acrylate, 1,1,1,3,3,3-hexafluoropropane-2-yl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 2,2,3,3-tetrafluoropropyl acrylate, 2,2,3,3,3-pentafluoropropyl acrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, hexafluorobutyl methacrylate, hexafluoroisopropyl acrylate, and 2,2,3,3,4,4,4-heptafluorobutyl methacrylate.
[0065] In one embodiment, the polymer monomer further comprises a silicon-containing monomer. In the present embodiment, the silicon-containing monomer can promote the migration of lithium ions and increase the migration speed of lithium ions in the electrolyte. Optionally, the silicon-containing monomer comprises vinyl trimethoxy silane, dimethoxy (methyl) (vinyl) silane, vinyl triethoxy silane, vinyl triisopropoxy silane, methoxy dimethyl (vinyl) silane, methyl vinyl diethoxy silane, vinyl dimethyl ethoxy silane, allyl trimethoxy silane, tri (2-methoxyethoxy) vinyl silane, vinyloxy trimethyl silane, allyl triethoxy silane, trimethoxy (7-octen-1-yl) silane, isopropenyl oxy trimethyl silane, trimethyl ((2-methylprop-1-ene-1-yl) oxy) silane, triphenoxy (vinyl) silane, vinyl pentamethyl disiloxane, vinyl tri (trimethylsiloxy) silane at least one.
[0066] In one embodiment, the mass percentage of the silicon-containing monomer in the polymer monomer is 30%-70%; optionally, the mass percentage of the silicon-containing monomer in the polymer monomer can be any one of 30%, 35%, 40%, 45%, 50%, 55%, 60%, 70%, etc. or a range between any two of them.
[0067] In one embodiment, the polymer monomer further comprises a sulfur-containing monomer. In this embodiment, the sulfur-containing monomer can make the generated polymer have a certain Young's modulus, increase the puncture strength and impact strength of the polymer, and improve the safety performance of the battery. Optionally, the sulfur-containing monomer comprises at least one of allyl ethyl sulfide, allyl methyl sulfide, allyl methyl disulfide, allyl propyl disulfide, and diallyl trisulfide.
[0068] In one embodiment, the mass percentage of the sulfur-containing monomer in the polymer monomer is 0-40%. Optionally, the mass percentage of the sulfur-containing monomer in the polymer monomer can be any one of 0, 5%, 10%, 15%, 20%, 25%, 30%, 40%, etc., or a range between any two.
[0069] In one embodiment, the electrolyte further includes a crosslinking agent, and the mass percentage of the crosslinking agent in the electrolyte is 0.1%-5%. Optionally, the mass percentage of the crosslinking agent in the electrolyte can be any one of 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, etc., or a range between any two.
[0070] In one embodiment, the crosslinking agent includes a sulfur-containing crosslinking agent, which can improve the migration rate and conduction efficiency of lithium ions in the electrolyte. Optionally, the sulfur-containing crosslinking agent includes at least one of propylene monosulfide, prop-2-ene-1-thiosulfinic acid S-allyl ester, diallyl trisulfide, and N,N-bis(acryloyl)cystamine.
[0071] In one embodiment, the crosslinking agent includes a silicon-containing crosslinking agent. In this embodiment, the silicon-containing crosslinking agent can promote the migration of lithium ions and increase the migration speed of lithium ions in the electrolyte. Optionally, the silicon-containing crosslinking agent includes at least one of trivinylethoxysilane, tetraethoxydivinyldisiloxane, tetramethyldivinyldisiloxane, and tetrakis(dimethylvinylsiloxy)silane.
[0072] In one embodiment, the electrolyte further includes an initiator, a lithium salt, an additive and inorganic conductive particles.
[0073] In one embodiment, the initiator includes at least one of N,N-azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, diethylhexyl oxydicarbonate, benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate.
[0074] In one embodiment, the mass percentage of the initiator in the electrolyte is 0.01%-1%. Optionally, the mass percentage of the initiator in the electrolyte can be any one of 0.01%, 0.02%, 0.05%, 0.07%, 1%, etc., or a range between any two of them.
[0075] In one embodiment, the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium tetrafluorooxalatophosphate, lithium bis(fluorobis(oxalatophosphate), lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate), and lithium difluorooxalatoborate.
[0076] In one embodiment, the mass percentage of lithium salt in the electrolyte is 10%-25%. Optionally, the mass percentage of lithium salt in the electrolyte can be any one of 10%, 14%, 16%, 18%, 20%, 23%, 25%, etc. or a range between any two.
[0077] In one embodiment, the additive includes at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, methylene disulfonate, vinyl sulfite, polyether sulfone, vinyl sulfate, and propenyl-1,3-sultone.
[0078] In one embodiment, the mass percentage of the additive in the electrolyte is 0.1%-5%. Optionally, the mass percentage of the additive in the electrolyte can be any one of 0.1%, 0.4%, 1%, 2%, 3%, 4%, 5%, etc., or a range between any two.
[0079] In one embodiment, the inorganic conductive particles include at least one of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate, lithium lanthanum titanate, silicon dioxide, and titanium dioxide. In this embodiment, on the one hand, the inorganic conductive particles can promote the transmission rate of lithium ions in the polymer, reduce the crystallinity of the polymer, and improve the ionic conductivity of the polymer; on the other hand, the inorganic conductive particles can increase the mechanical strength of the polymer, increase the battery's anti-extrusion performance, anti-heavy impact performance, and acupuncture performance.
[0080] In one embodiment, the average particle size of the inorganic conductive particles is 5nm-350nm. Optionally, the average particle size of the inorganic conductive particles can be any one of 5nm, 10nm, 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, etc. or a range between any two. In this embodiment, if the average particle size of the inorganic conductive particles is too large, the inorganic conductive particles are prone to sedimentation in the electrolyte, and the inorganic conductive particles in the electrolyte are unevenly distributed, affecting the conductive properties and ion transmission efficiency of the electrolyte; if the average particle size of the inorganic conductive particles is too small, the inorganic conductive particles are prone to agglomeration in the electrolyte, affecting the conductive properties and ion transmission efficiency of the electrolyte.
[0081] In one embodiment, the mass percentage of the inorganic conductive particles in the electrolyte is 0.1%-10%. Optionally, the mass percentage of the inorganic conductive particles in the electrolyte can be any one of 0.1%, 0.4%, 1%, 2%, 4%, 6%, 8%, 10%, etc., or a range between any two.
[0082] The present application also provides an electrolyte, which is prepared from the above-mentioned electrolyte.
[0083] In this embodiment, the electrolyte used to prepare the electrolyte includes a first solvent, a second solvent and a third solvent. The first solvent has a lower viscosity, the second solvent has a higher polarity, and the third solvent contains fluorine atoms. Through the synergistic effect between the first solvent, the second solvent and the third solvent, high-polarity components such as fluorine-containing monomers have better solubility and dispersibility in the electrolyte. At the same time, the electrolyte has a lower viscosity, and the electrolyte can evenly and quickly infiltrate the battery cell, thereby improving the wetting effect of the electrolyte and the diffusibility of each component in the electrolyte in the battery cell.
[0084] The present application also provides a method for preparing an electrolyte, comprising the following steps:
[0085] S1, providing the electrolyte as described above;
[0086] S2. Inject the electrolyte into the battery cell, let it stand, heat and solidify to obtain the electrolyte.
[0087] In one embodiment, the preparation method of the electrolyte includes the following steps: mixing a formulated amount of polymer monomers, an organic solvent and other raw materials to obtain an electrolyte; wherein the polymer monomer includes a fluorine-containing monomer, the organic solvent includes a first solvent, a second solvent and a third solvent, the viscosity of the first solvent is 0.1-0.6mPa.s, the dielectric constant of the second solvent is 20-100, and the third solvent is a fluorine-containing solvent; based on the total volume of the organic solvent as 100%, the volume percentage of the first solvent in the organic solvent is 30%-80%, the volume percentage of the second solvent in the organic solvent is 5%-50%, and the volume percentage of the third solvent in the organic solvent is 5%-40%.
[0088] In one embodiment, other raw materials further include a formulated amount of sulfur-containing monomers, silicon-containing monomers, cross-linking agents, initiators, lithium salts, additives, and inorganic conductive particles.
[0089] In one embodiment, the mixing may be performed in an argon atmosphere or a nitrogen atmosphere, which is not limited herein.
[0090] In one embodiment, the mixing temperature is 21° C.-25° C. Optionally, the mixing temperature can be any one of 21° C., 22° C., 22° C., 24° C., 25° C., etc., or a range between any two thereof.
[0091] In one embodiment, the mixing time is 4h-24h; optionally, the mixing time can be any one of 4h, 6h, 8h, 10h, 14h, 18h, 20h, 24h, etc. or a range between any two of them.
[0092] In one embodiment, the standing temperature is 21° C.-25° C. Optionally, the standing temperature may be any one of 21° C., 22° C., 22° C., 24° C., 25° C., etc., or a range between any two of them.
[0093] In one embodiment, the standing time is 24 hours to 72 hours. Optionally, the standing time can be any one of 24 hours, 30 hours, 35 hours, 40 hours, 45 hours, 50 hours, 60 hours, 70 hours, 72 hours, etc., or a range between any two of them.
[0094] In one embodiment, the temperature of the heating and curing is 45° C.-120° C. Optionally, the temperature of the heating and curing can be any one of 45° C., 55° C., 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., 120° C., etc., or a range between any two thereof.
[0095] In one embodiment, the heating and curing time is 4 hours to 24 hours. Optionally, the heating and curing time can be any one of 4 hours, 6 hours, 9 hours, 13 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, etc., or a range between any two of them.
[0096] The present application also provides a lithium-ion battery, which includes the electrolyte as described above or the electrolyte prepared by the method as described above.
[0097] In this embodiment, the type of lithium-ion battery is not limited, and the lithium-ion battery can be one of a ternary soft-pack battery, a ternary steel-shell battery, a lithium cobalt oxide soft-pack battery, and a lithium cobalt oxide steel-shell battery.
[0098] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present application are described in detail as follows:
[0099] Example 1
[0100] This embodiment provides an electrolyte solution, including: a polymer monomer, an organic solvent, a lithium salt, an additive, inorganic conductive particles, an initiator, and a cross-linking agent;
[0101] The mass percentage of the polymer monomer in the electrolyte is 23%, and the polymer monomer is composed of 2,2-trifluoroethyl methacrylate, vinyl trimethoxy silane and allyl ethyl sulfide. Taking the total mass of the polymer monomer as 100%, the volume percentage of 2,2-trifluoroethyl methacrylate in the polymer monomer is 50%, the volume percentage of vinyl trimethoxy silane in the polymer monomer is 40%, and the volume percentage of allyl ethyl sulfide in the polymer monomer is 10%;
[0102] The mass percentage of the organic solvent in the electrolyte is 51.5%, and the organic solvent consists of a first solvent, a second solvent and a third solvent. The first solvent is ethylene glycol dimethyl ether, and the viscosity of ethylene glycol dimethyl ether at room temperature is 0.46 mPa.s. The second solvent is adiponitrile, and the dielectric constant of adiponitrile at room temperature is 30. The third solvent is ethyl difluoroacetate. Based on the total volume of the organic solvent as 100%, the volume percentage of the first solvent in the organic solvent is 55%, the volume percentage of the second solvent in the organic solvent is 15%, and the volume percentage of the third solvent in the organic solvent is 30%.
[0103] The lithium salt is lithium hexafluorophosphate, and the mass percentage of the lithium salt in the electrolyte is 15%;
[0104] The additive is vinylene carbonate, and the mass percentage of the additive in the electrolyte is 3%;
[0105] The initiator is N,N-azobisisobutyronitrile, and the mass percentage of the initiator in the electrolyte is 0.5%;
[0106] The inorganic conductive nanoparticles are lithium lanthanum zirconium oxide, and the mass percentage of the inorganic conductive nanoparticles in the electrolyte is 5%;
[0107] The cross-linking agent is pentaerythritol tetraacrylate, and the mass percentage of the cross-linking agent in the electrolyte is 2%.
[0108] This embodiment also provides a method for preparing a lithium ion battery, the specific method of which is as follows:
[0109] (1) A negative electrode material graphite, a conductive agent acetylene black, and a binder sodium carboxymethyl cellulose and styrene-butadiene rubber were prepared into a slurry in a mass percentage of 94:1:2:3, and the slurry was coated on a copper foil current collector and dried to obtain a negative electrode sheet; a positive electrode material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2), acetylene black as a conductive agent and polyvinylidene fluoride as a binder are prepared into a slurry in a mass ratio of 94:3:3 and coated on an aluminum foil current collector, and dried to obtain a positive electrode sheet. The positive electrode sheet, the negative electrode sheet and the separator are assembled to obtain a battery cell.
[0110] (2) In an argon atmosphere, the polymer monomer, organic solvent, lithium salt, additive, inorganic conductive particles, initiator and cross-linking agent in the above-mentioned formula are mixed at an ambient temperature of 25° C. to obtain an electrolyte.
[0111] (2) Injecting electrolyte into the battery cell, vacuum packaging, standing, and heating to cure, to obtain a lithium ion battery, wherein the vacuum degree of the vacuum packaging is -87 kPa, the standing temperature is 25° C., the standing time is 24 h, the heating curing temperature is 75° C., and the heating curing time is 20 h.
[0112] Example 2
[0113] The difference between Example 2 and Example 1 is:
[0114] The first solvent is 2-methyltetrahydrofuran, and the viscosity of 2-methyltetrahydrofuran at room temperature is 0.47 mPa.s. The rest is the same as in Example 1.
[0115] Example 3
[0116] The difference between Example 3 and Example 1 is that:
[0117] The second solvent is methylglutaronitrile, and the dielectric constant of methylglutaronitrile at room temperature is 37. The rest is the same as in Example 1.
[0118] Example 4
[0119] The difference between Example 4 and Example 1 is:
[0120] The third solvent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and the rest is the same as in Example 1.
[0121] Example 5
[0122] The difference between Example 5 and Example 1 is:
[0123] The volume percentage of ethylene glycol dimethyl ether in the organic solvent is 50%, the volume percentage of adiponitrile in the organic solvent is 25%, the volume percentage of ethyl difluoroacetate in the organic solvent is 25%, and the rest is the same as in Example 1.
[0124] Example 6
[0125] The difference between Example 6 and Example 1 is:
[0126] The volume percentage of ethylene glycol dimethyl ether in the organic solvent is 30%, the volume percentage of adiponitrile in the organic solvent is 50%, the volume percentage of ethyl difluoroacetate in the organic solvent is 20%, and the rest is the same as in Example 1.
[0127] Example 7
[0128] The difference between Example 7 and Example 1 is:
[0129] The volume percentage of ethylene glycol dimethyl ether in the organic solvent is 80%, the volume percentage of adiponitrile in the organic solvent is 5%, the volume percentage of ethyl difluoroacetate in the organic solvent is 15%, and the rest is the same as in Example 1.
[0130] Example 8
[0131] The difference between Example 8 and Example 1 is:
[0132] The volume percentage of ethylene glycol dimethyl ether in the organic solvent is 55%, the volume percentage of adiponitrile in the organic solvent is 40%, the volume percentage of ethyl difluoroacetate in the organic solvent is 5%, and the rest is the same as in Example 1.
[0133] Example 9
[0134] The difference between Example 9 and Example 1 is:
[0135] The volume percentage of ethylene glycol dimethyl ether in the organic solvent is 55%, the volume percentage of adiponitrile in the organic solvent is 5%, the volume percentage of ethyl difluoroacetate in the organic solvent is 40%, and the rest is the same as in Example 1.
[0136] Comparative Example 1
[0137] The difference between Comparative Example 1 and Example 1 is:
[0138] The organic solvent is composed of ethylene glycol dimethyl ether and adiponitrile. Taking the total volume of the organic solvent as 100%, the volume percentage of ethylene glycol dimethyl ether in the organic solvent is 70%, and the volume percentage of adiponitrile in the organic solvent is 30%. The rest is the same as in Example 1.
[0139] Comparative Example 2
[0140] The difference between Comparative Example 2 and Example 1 is:
[0141] The organic solvent consists of ethylene glycol dimethyl ether and ethyl difluoroacetate. Taking the total volume of the organic solvent as 100%, the volume percentage of ethylene glycol dimethyl ether in the organic solvent is 70%, and the volume percentage of ethyl difluoroacetate in the organic solvent is 30%. The rest is the same as in Example 1.
[0142] Comparative Example 3
[0143] The difference between Comparative Example 3 and Example 1 is:
[0144] The organic solvent consists of adiponitrile and ethyl difluoroacetate. Taking the total volume of the organic solvent as 100%, the volume percentage of adiponitrile in the organic solvent is 70%, the volume percentage of ethyl difluoroacetate in the organic solvent is 30%, and the rest is the same as in Example 1.
[0145] Comparative Example 4
[0146] The difference between Comparative Example 4 and Example 1 is:
[0147] The organic solvent consists of ethylene glycol dimethyl ether, and the volume percentage of ethylene glycol dimethyl ether in the organic solvent is 100%. The rest is the same as in Example 1.
[0148] Comparative Example 5
[0149] The difference between Comparative Example 5 and Example 1 is:
[0150] The organic solvent consists of ethylene glycol dimethyl ether, adiponitrile and ethyl difluoroacetate. Taking the total volume of the organic solvent as 100%, the volume percentage of ethylene glycol dimethyl ether in the organic solvent is 28%, the volume percentage of adiponitrile in the organic solvent is 40%, and the volume percentage of ethyl difluoroacetate in the organic solvent is 32%.
[0151] Comparative Example 6
[0152] The difference between Comparative Example 6 and Example 1 is:
[0153] The organic solvent consists of ethylene glycol dimethyl ether, adiponitrile and ethyl difluoroacetate. Taking the total volume of the organic solvent as 100%, the volume percentage of ethylene glycol dimethyl ether in the organic solvent is 65%, the volume percentage of adiponitrile in the organic solvent is 4%, and the volume percentage of ethyl difluoroacetate in the organic solvent is 31%.
[0154] Comparative Example 7
[0155] The difference between Comparative Example 7 and Example 1 is:
[0156] The organic solvent consists of ethylene glycol dimethyl ether, adiponitrile and ethyl difluoroacetate. Taking the total volume of the organic solvent as 100%, the volume percentage of ethylene glycol dimethyl ether in the organic solvent is 35%, the volume percentage of adiponitrile in the organic solvent is 15%, and the volume percentage of ethyl difluoroacetate in the organic solvent is 50%.
[0157] Comparative Example 8
[0158] The difference between Comparative Example 8 and Example 1 is:
[0159] The organic solvent consists of ethylene glycol dimethyl ether, adiponitrile and ethyl difluoroacetate. Taking the total volume of the organic solvent as 100%, the volume percentage of ethylene glycol dimethyl ether in the organic solvent is 80%, the volume percentage of adiponitrile in the organic solvent is 16%, and the volume percentage of ethyl difluoroacetate in the organic solvent is 4%.
[0160] Test Method
[0161] The lithium ion batteries obtained in Examples 1 to 9 and Comparative Examples 1 to 8 were subjected to electrochemical performance tests and needle puncture tests, and the specific methods are as follows:
[0162] (1) Cycle performance: Full battery test at 25°C with a constant current and constant voltage charge at a current density of 1C and a constant current pulse discharge at a current density of 6C (discharge for 5s, rest for 10s, until the voltage is lower than 3.3V after resting for 10s). The charge and discharge voltage window is 3.3V-4.2V.
[0163] (2) Rate performance: The lithium-ion battery is charged at a current density of 1C with constant current and constant voltage, and discharged at a current density of 6C with constant current pulse discharge (discharge for 5 seconds, leave for 10 seconds, until the voltage is lower than 3.3V after 10 seconds of leaving). The charge and discharge voltage window is 3.3V-4.2V.
[0164] (3) Needle puncture test: After the lithium-ion battery is fully charged, a 3 mm diameter high-temperature resistant steel needle (the cone angle of the needle tip is 45°-60°, the needle surface is smooth, free of rust, oxide layer and oil) is used to penetrate the battery at a speed of (25±5) mm / s from a direction perpendicular to the surface of the battery cell. The penetration position should be close to the geometric center of the punctured surface. The steel needle stays in the battery and is observed for 1 hour.
[0165] The test results are shown in Table 1 below:
[0166] Table 1
[0167]
[0168] Based on the test results of the above embodiments and comparative examples, it can be seen that the lithium-ion batteries prepared in Examples 1 to 9 have good rate performance, excellent cycle performance and high puncture pass rate, which shows that the organic solvent of the electrolyte of the present invention includes a first solvent, a second solvent and a third solvent. Through the synergistic effect between the first solvent, the second solvent and the third solvent, the high polarity components such as fluorine-containing monomers have good solubility and dispersibility in the electrolyte. At the same time, the electrolyte has a lower viscosity, and the electrolyte can evenly and quickly infiltrate the battery cell, thereby improving the wetting effect of the electrolyte and the diffusibility of each component in the electrolyte in the battery cell, and improving the rate performance, cycle performance and safety performance of the battery.
[0169] From the comparison of Examples 1 to 9 and Comparative Examples 1 to 4, it can be seen that the electrolytes of Examples 1 to 9 simultaneously contain the first solvent, the second solvent and the third solvent. The synergistic effect between the first solvent, the second solvent and the third solvent can effectively improve the polarity of the electrolyte. At the same time, the electrolyte has a lower viscosity, and the electrolyte can evenly and quickly infiltrate the battery cell, thereby improving the wetting effect of the electrolyte and the diffusibility of each component in the electrolyte in the battery cell.
[0170] From the comparison between Examples 1 to 9 and Comparative Examples 5 to 8, it can be seen that controlling the contents of the first solvent, the second solvent and the third solvent within an appropriate range can further ensure the rate performance, cycle performance and safety performance of the battery.
[0171] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. An electrolyte, characterized in that: include: polymer monomers and organic solvents; The polymer monomer includes a fluorine-containing monomer; The organic solvent comprises a first solvent, a second solvent and a third solvent, the viscosity of the first solvent is 0.1-0.6 mPa.s, the dielectric constant of the second solvent is 20-100, and the third solvent is a fluorine-containing solvent; Taking the total volume of the organic solvent as 100%, the volume percentage of the first solvent in the organic solvent is 30%-80%, the volume percentage of the second solvent in the organic solvent is 5%-50%, and the volume percentage of the third solvent in the organic solvent is 5%-40%.
2. The electrolyte according to claim 1, characterized in that The mass percentage of the organic solvent in the electrolyte is 40%-84%.
3. The electrolyte according to claim 1 or 2, characterized in that The first solvent comprises at least one of acetonitrile, propionitrile, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, ethyl acetate, methyl acetate, methyl formate, ethyl formate, propyl formate, isopropyl formate, dimethanol formal, ethylene glycol dimethyl ether, and ethylene glycol ethyl formate; and / or The second solvent comprises at least one of methylglutaronitrile, glutaronitrile, adiponitrile, succinonitrile, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfone, dimethyl sulfoxide, diethyl sulfone, and sulfolane; and / or The third solvent includes at least one of ethyl fluoroacetate, ethyl difluoroacetate, ethyl trifluoroacetate, N,N-dimethyltrifluoroacetamide, trifluorobenzene, 1,2,3,5-tetrafluorobenzene, α,α,α-trifluorotoluene, 1,2-difluorobenzene, 1,3-difluorobenzene, fluoroethylene carbonate, 2,3-difluorophenyl ether, 2-trifluoromethyl ethylene oxide, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether, methyl nonafluorobutyl ether, 1,1,1,2,3,4,4,5,5,5-decafluoro-3-methoxy-2-trifluoromethylpentane, trimethylsilyl trifluoromethanesulfonate, and dimethoxymethyl (3,3,3-trifluoropropyl) silicon.
4. The electrolyte according to claim 1 or 2, characterized in that The mass percentage of the polymer monomer in the electrolyte is 5%-60%; and / or The mass percentage of the fluorine-containing monomer in the polymer monomer is 30%-70%; and / or The fluorine-containing monomer includes at least one of 2,2-trifluoroethyl methacrylate, 2,2,2-trifluoroethyl acrylate, 1,1,1,3,3,3-hexafluoropropane-2-yl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 2,2,3,3-tetrafluoropropyl acrylate, 2,2,3,3,3-pentafluoropropyl acrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, hexafluorobutyl methacrylate, hexafluoroisopropyl acrylate, and 2,2,3,3,4,4,4-heptafluorobutyl methacrylate; and / or The polymer monomers further include silicon-containing monomers and / or sulfur-containing monomers.
5. The electrolyte according to claim 4, characterized in that The silicon-containing monomer includes at least one of vinyl trimethoxysilane, dimethoxy (methyl) (vinyl) silane, vinyl triethoxy silane, vinyl triisopropoxy silane, methoxydimethyl (vinyl) silane, methyl vinyl diethoxy silane, vinyl dimethylethoxy silane, allyl trimethoxy silane, tris (2-methoxyethoxy) vinyl silane, vinyloxy trimethyl silane, allyl triethoxy silane, trimethoxy (7-octen-1-yl) silane, isopropenyloxy trimethyl silane, trimethyl ((2-methylprop-1-en-1-yl)oxy) silane, triphenoxy (vinyl) silane, vinyl pentamethyl disiloxane, and vinyl tris (trimethylsiloxy) silane; and / or The sulfur-containing monomer includes at least one of allyl ethyl sulfide, allyl methyl sulfide, allyl methyl disulfide, allyl propyl disulfide, and diallyl trisulfide; and / or The mass percentage of the silicon-containing monomer in the polymer monomer is 30%-70%; and / or The mass percentage of the sulfur-containing monomer in the polymer monomer is 0-40%.
6. The electrolyte according to claim 1 or 2, characterized in that The electrolyte further includes a cross-linking agent, and the cross-linking agent includes a sulfur-containing cross-linking agent and / or a silicon-containing cross-linking agent.
7. The electrolyte according to claim 6, characterized in that The silicon-containing crosslinking agent comprises at least one of trivinylethoxysilane, tetraethoxydivinyldisiloxane, tetramethyldivinyldisiloxane and tetrakis(dimethylvinylsiloxy)silane; and / or The sulfur-containing crosslinking agent includes at least one of diallyl monosulfide, prop-2-ene-1-thiosulfinic acid S-allyl ester, diallyl trisulfide, and N,N-bis(acryloyl)cystamine; and / or The mass percentage of the cross-linking agent in the electrolyte is 0.1%-5%.
8. The electrolyte according to claim 1 or 2, characterized in that: The electrolyte further comprises an initiator, a lithium salt, an additive and inorganic conductive particles.
9. The electrolyte according to claim 8, characterized in that The initiator comprises at least one of N,N-azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, diethylhexyl oxydicarbonate, benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate; and / or The mass percentage of the initiator in the electrolyte is 0.01%-1%; and / or The lithium salt comprises at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium tetrafluorooxalatophosphate, lithium bis(fluorobis(oxalatophosphate), lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate), and lithium difluorooxalatoborate; and / or The mass percentage of the lithium salt in the electrolyte is 10%-25%; and / or The additive comprises at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, methylene disulfonate, vinyl sulfite, polyether sulfone, vinyl sulfate, and propenyl-1,3-sultone; and / or The mass percentage of the additive in the electrolyte is 0.1%-5%; and / or The inorganic conductive particles include at least one of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate, lithium lanthanum titanate, silicon dioxide, and titanium dioxide; and / or The average particle size of the inorganic conductive particles is 5nm-350nm; and / or The mass percentage of the inorganic conductive particles in the electrolyte is 0.1%-10%.
10. An electrolyte, characterized in that The electrolyte is prepared from the electrolyte according to any one of claims 1 to 9.
11. A method for preparing an electrolyte, characterized in that: The preparation method of the electrolyte comprises the following steps: Providing an electrolyte according to any one of claims 1 to 9; The electrolyte is injected into the battery cell, left to stand, and heated to solidify to obtain the electrolyte.
12. The preparation method according to claim 11, characterized in that: The preparation method of the electrolyte comprises the following steps: mixing the polymer monomer, organic solvent and other raw materials in a prescribed amount to obtain the electrolyte; Wherein, the polymer monomer includes a fluorine-containing monomer; The organic solvent comprises a first solvent, a second solvent and a third solvent, the viscosity of the first solvent is 0.1-0.6 mPa.s, the dielectric constant of the second solvent is 20-100, and the third solvent is a fluorine-containing solvent; Taking the total volume of the organic solvent as 100%, the volume percentage of the first solvent in the organic solvent is 30%-80%, the volume percentage of the second solvent in the organic solvent is 5%-50%, and the volume percentage of the third solvent in the organic solvent is 5%-40%.
13. The preparation method according to claim 12, characterized in that: The other raw materials also include a formula amount of sulfur-containing monomers, silicon-containing monomers, cross-linking agents, initiators, lithium salts, additives and inorganic conductive particles; and / or The mixing is carried out in an argon atmosphere or a nitrogen atmosphere, and / or the mixing temperature is 21° C.-25° C., and / or the mixing time is 4 h-24 h; and / or The standing temperature is 21°C-25°C, and / or the standing time is 24h-72h; and / or The temperature of the heating and curing is 45° C.-120° C., and / or the time of the heating and curing is 4 h-24 h.
14. A lithium ion battery, characterized in that: The lithium-ion battery comprises the electrolyte according to claim 10 or an electrolyte prepared by the method according to any one of claims 11 to 13.
Citation Information
Cited By
Solid-liquid mixed aluminum electrolytic capacitor suitable for low-pressure environment
CN120600539A
Solid-liquid mixed aluminum electrolytic capacitor suitable for low pressure environment
CN120600539B